Tren dan Kesenjangan Penelitian Pendidikan Jasmani untuk Kesejahteraan Psikologis Siswa Asia Berbasis Bibliometrik - Naufal Nur Fadhillah Karim; Yusuf Hidayat; Burhan Hambali (Jayapangus Press, 2026)
Mental health issues among students in Asia have been increasing due to high academic pressure and the prolonged impacts of the COVID-19 pandemic, while physical education is recognized as a potential school-based intervention for enhancing psychological well-being. However, no comprehensive bibliometric mapping exists for this research area focusing on student populations in the Asian context. This study aimed to map publication trends, country and institutional productivity, thematic evolution, international collaboration patterns, and research gaps in physical education and student psychological well-being research across Asia. A bibliometric analysis was conducted on 983 articles retrieved from Scopus and PubMed databases covering the period 2015-2024, selected through a systematic screening process following PRISMA guidelines and analyzed using Biblioshiny software. Results revealed rapid publication growth of 41.74% annually, coinciding with increased academic attention during the COVID-19 pandemic, reaching 277 articles in 2024. China dominated with 54.18% of total publications, followed by Indonesia (7.03%) and Japan (6.21%), while South Asian countries remained substantially underrepresented. Two thematic clusters were identified: a core cluster focusing on school-age populations and physical education, and an emerging cluster centered on college students and pandemic-related mental health. Intra-Asian collaboration remained limited, with Australia and Canada serving as external collaboration hubs. Significant research gaps were identified in specific pedagogical approaches including outdoor education, cooperative learning, life skills, adventure education, and sport education model. Future research should prioritize expanding studies in underrepresented Asian countries, strengthening intra-Asian collaboration networks, and exploring innovative pedagogical approaches as psychological well-being interventions for students across diverse Asian educational contexts.